Characterization of Salmonella spp. Isolates from Swine: Virulence and Antimicrobial Resistance - Thao, Pham Thi Thanh (Multidisciplinary Digital Publishing Institute, 2022)
Salmonella is one of the most important zoonotic pathogens worldwide. Swine represent typical reservoirs of this bacterium and a frequent source of human infection. Some intrinsic traits make some serovars or strains more virulent than others. Twenty-nine Salmonella spp. isolated from pigs belonging to 16 different serovars were analyzed for gastric acid environment resistance, presence of virulence genes (mgtC, rhuM, pipB, sopB, spvRBC, gipA, sodCI, sopE), antimicrobial resistance and presence of antimicrobial resistance genes (blaTEM, blaPSE-1, aadA1, aadA2, aphA1-lab, strA-strB, tetA, tetB, tetC, tetG, sul1, sul2, sul3). A percentage of 44.83% of strains showed constitutive and inducible gastric acid resistance, whereas 37.93% of strains became resistant only after induction. The genes sopB, pipB and mgtC were the most often detected, with 79.31%, 48.28% and 37.93% of positive strains, respectively. Salmonella virulence plasmid genes were detected in a S. enterica sup. houtenae ser. 40:z4,z23:-strain. Fifteen different virulence profiles were identified: one isolate (ser. Typhimurium) was positive for 6 genes, and 6 isolates (3 ser. Typhimurium, 2 ser. Typhimurium monophasic variant and 1 ser. Choleraesuis) scored positive for 5 genes. None of the isolates resulted resistant to cefotaxime and ciprofloxacin, while all isolates were susceptible to ceftazidime, colistin and gentamycin. Many strains were resistant to sulfonamide (75.86%), tetracycline (51.72%), streptomycin (48.28%) and ampicillin (31.03%). Twenty different resisto-types were identified. Six strains (4 ser. Typhimurium, 1 ser. Derby and 1 ser. Typhimurium monophasic variant) showed the ASSuT profile. Most detected resistance genes sul2 (34.48%), tetA (27.58%) and strA-strB (27.58%). Great variability was observed in analyzed strains. S. ser. Typhimurium was confirmed as one of the most virulent serovars. T